Handbook of Development Economics / Vol. 3B - Chenery, Hollis B.; Srinivasan, T. N.; Behrman, J. R. (San Diego : North Holland, 1995)
Annotation This third volume of the Handbook of Development Economics employs rigorous theoretical and empirical frameworks. It focuses on policy and includes material from unpublished and not generally available sources. Inparticular, it covers analytical and policy issues arising from the collapse of the paradigm of development based on import-substituting-industrialization in most developing countries; and the demise of centrally planned economies ofEastern Europe and the Soviet Union. The volume also deals with the increasing recognition of the importance of micro behavioral responses to a range of incentives and unobserved factors both for analysis and for policy formulation.It discusses the ongoing process of economic reforms in developing countries by reducing state involvement in the economy through privatization, opening up the economy much more to foreign trade and investment and allowing market forces and the private sector to guide resource allocation to a much greater extent. As well as updating developments on topics which were included in the earlier volumes, this Handbook also includes different topics, such as econometric andother empirical modeling tools for development analysis and the role of technology in the development process.As in the previous volumes of the series, the chapters in this Handbook provide self-contained surveys summarizing not only received knowledge but also recent developments. Each chapter is also a definitive source, reference and teaching supplement for use by researchers and advanced graduate students.
Scholarly & Professional